2010
DOI: 10.1016/j.joen.2009.10.028
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Spectroscopic Analysis to Determine Whether Para-Chloroaniline Is Produced from Mixing Sodium Hypochlorite and Chlorhexidine

Abstract: Introduction-The purpose of this in vitro study was to determine whether para-chloroaniline (PCA) is formed through the reaction of mixing sodium hypochlorite (NaOCl) and chlorhexidine (CHX).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1
9

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(79 citation statements)
references
References 24 publications
1
68
1
9
Order By: Relevance
“…The presence of chlorine in the para position of the benzene ring was finally confirmed using the nuclear magnetic resonance imaging technique 2 . However, Thomas and Sem 15 claimed that the reaction mixture of NaOCl and CHX does not produce PCA in any measurable quantity, and further investigation is needed to determine the chemical composition of the brown precipitate 15 . In addition, Nowicki and Sem 21 using one dimensional and dual dimensional NMR found that the precipitate consists of at least 2 sub-products of CHX, smaller than CHX, neither of them being PCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of chlorine in the para position of the benzene ring was finally confirmed using the nuclear magnetic resonance imaging technique 2 . However, Thomas and Sem 15 claimed that the reaction mixture of NaOCl and CHX does not produce PCA in any measurable quantity, and further investigation is needed to determine the chemical composition of the brown precipitate 15 . In addition, Nowicki and Sem 21 using one dimensional and dual dimensional NMR found that the precipitate consists of at least 2 sub-products of CHX, smaller than CHX, neither of them being PCA.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a combination of NaOCl and CHX has been recommended to enhance their properties, on the basis that the antimicrobial effect of 2.5% NaOCl and 0.2% CHX used in combination is better than that of either solution alone 10 . However, this association forms a dense, orange-brown precipitate that stains the walls of the pulp chamber 2,7,15,16 . This insoluble precipitate is difficult to remove from the canal, occludes the dentinal tubules 3 thus preventing penetration of the intra-canal medicaments and compromises the seal of the obturated root canal 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Osim toga, ustanovljeno je da se ovaj talog sastoji od para-hloranilina (PCA), za koga je dokazano da deluje toksično u eksperimentima subkutane implantacije kod pacova 30 . Literaturni podaci ukazuju ne samo na toksičnost PCA, nego i na toksičnost njegovih degradacionih produkata 31,32,33 . Para-hloranilin se inače koristi kao pesticid i može imati kancerogeno dejstvo 34 .…”
Section: Interakcije Između Iriganasaunclassified
“…Literature data indicate not only the toxicity of PCA, but also the toxicity of its degradation products 31,32,33 . Para-chloroaniline is used as a pesticide and can have carcinogenic effect 34 .…”
Section: Korekcija Protokola Irigacijementioning
confidence: 99%
“…Há uma grande discussão sobre a associação, pois estas substâncias reagem formando um precipitado de cor marrom, não solúvel em água (Siqueira Jr, 1997;Kuruvilla;Kamath, 1998;White et al, 1999;VivacquaGomes et al, 2002;Zenhder, 2006;Basrani et al, 2007;Marchesan et al, 2007;Bui et Krishnamurthy;Sudhakaran, 2010;Thomas;Sem, 2010;Nowicki;Sem, 2011).…”
Section: Nacional De Toxicologia Da Agência De Proteção Ambiental (Epunclassified